Effect of three different intracanal medications on canal wall cleanliness and radicular dentin microhardness - Amira Ibrahim Mohamed; Soha Adel Abdou; Yousra Aly (Journal of the Arab Society for Medical Research)
Background/aim Complete removal of intracanal medication from the canals before root canal obturation is an essential step. This research was conducted to comparatively assess the remaining debris after the removal of three intracanal medications: silver nanoparticles (AgNPs) paste, silver nanoparticles (AgNPs) with curcumin paste, and calcium hydroxide (Ca(OH)2) paste on the root canal walls and their effect on microhardness of radicular dentin. Materials and methods Thirty human extracted single-rooted teeth were selected from the National Research Centre Dental Clinic, Egypt. The crowns of the teeth were decapitated at the cementoenamel junction. All root canals were mechanically prepared. The specimens were randomly divided into three groups (each = 10) according to the type of medication used. Group A: AgNPs paste. Group B: AgNPs with curcumin paste. Group C: Ca(OH)2 paste. Intracanal medications were injected into the root canals and all specimens were incubated at 37°C for 7 days, then the intracanal medications were removed from the root canals and specimens were longitudinally sectioned. One-half of each specimen was examined under a stereomicroscope to evaluate the amount of remaining debris. The other half of each specimen was used to measure dentin microhardness using the Vickers Microhardness Tester. Statistical analysis was done. Results AgNPs paste showed a significantly low mean value of the remaining debris than AgNPs with curcumin paste, while Ca(OH)2 paste had a significantly highest mean value of the remaining debris than AgNPs paste alone or mixed with curcumin. AgNPs paste had the highest significant mean value of microhardness, then AgNPs with curcumin paste, while Ca(OH)2 paste had a significantly lowest mean value of microhardness. Conclusion AgNPs paste and AgNPs with curcumin paste used as intracanal medications were removed from the root canals with a minimal amount of the remaining debris and less effect on dentin microhardness than the Ca(OH)2 paste.